Avaliação da eficácia do extrato de óleo insaponificavel de abacate e soja (Piascledine) no tratamento de doença periodontal induzida em ratos com artrite - Tsurumaki, Jackeline do Nascimento [UNESP] (2014)
The avocado/soybean unsaponifiables(ASU) is a drug that has been used for the treatment of rheumatoid arthritis(AR) and other connective tissue disorders due to their potent anti-inflammatory and analgesic effect and antioxidant. Thus, the aim of this study was to evaluate the effect of this drug on the treatment of the ligature-induced periodontitis in rats with experimental arthritis. Sixty rats were used in this experiment. The arthritis was induced in thirty rats by injection of specific antigen (AIA) and the periodontitis was induced in all the rats by a insertion of a cotton ligature in the periodontal sulcus of the second upper molar. The ligatures removal and the scaling was performed 7 days after the ligatures placement. The animals were randomly divided in four groups: Control (CTR), ASU, ASU/AR and AR. The animals were euthanized 7, 15 and 30 days after the treatments. The maxilla’s and the joint of the front paw was removed to perform the analysis. The percentage of bone tissue in the proximal were analyzed by the micro CT. No statistical differences were detected between the groups. Regarding the intragroup analysis it was showed an enhance on the bone volume in the ASU/AR at 30 days compared with the period of 7 days, and an improve in bone volume the AR at 30 days compared with the period of 15 days. The descriptive histology showed that all the groups presented a mild inflammatory infiltrate, disorganization of collagen fibers and cementum integrity. In conclusion, the consumption of the ASU did not add any additional effect on the periodontal healing after the treatment of the ligature-induced periodontitis in rats with/without experimental arthritis.